Micro-RNA signatures in monozygotic twins discordant for congenital heart defects - Abu-Halima, Masood S.; Henn, Dominic (PLOS ONE, 2019)
Background MicroRNAs (miRNAs) are small RNAs regulating gene expression post-transcriptionally. Recent studies demonstrated that miRNAs are involved in the development of congenital heart defects (CHD). In this study, we aimed at identifying the specific patterns of miRNAs in blood of monozygotic twin pairs discordant for CHD and to assess whether miRNAs might be involved in the development or reflect the consequences of CHD. Methods miRNA microarray analysis and Real-Time Quantitative PCR (RT-qPCR) were employed to determine the miRNA abundance level from 12 monozygotic twins discordant for CHD and their non-CHD co-twins (n = 12). Enrichment analyses of altered miRNAs were performed using bioinformatics tools. Results Compared with non-CHD co-twins, profiling analysis indicated 34 miRNAs with a significant difference in abundance level (p<0.05, fold change ≥ 1.3), of which 11 miRNAs were up-regulated and 23 miRNAs were down-regulated. Seven miRNAs were validated with RT-qPCR including miR-511-3p, miR-1306-5p, miR-421, miR-4707-3p, miR-4732-3p, miR-5189-3p, and miR-890, and the results were consistent with microarray analysis. Five miRNAs namely miR-511-3p, miR-1306-5p, miR-4732-3p, miR-5189-3p, and miR-890 were found to be significantly up-regulated in twins < 10 years old. Bioinformatics analysis showed that the 7 validated miRNAs were involved in phosphatidylinositol signaling, gap junction signaling, and adrenergic signaling in cardiomyocytes. Conclusions Our data show deregulated miRNA abundance levels in the peripheral blood of monozygotic twins discordant for CHD, and identify new candidates for further analysis, which may contribute to understanding the development of CHD in the future. Bioinformatics analysis indicated that the target genes of these miRNAs are likely involved in signaling and communication of cardiomyocytes.
Gesehen am 01.04.2020